Pendampingan Pemasaran Digital Hasil Usaha Badan Usaha Milik Desa “Selo Angon Makmur” dalam Pemberdayaan Masyarakat Terdampak Pandemi Covid-19 - Moh Padil; Mohammad Miftahusyai’an; Galih Puji Mulyoto (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2021)
: The purpose of this community service is 1) Formulating and formulating digital marketing training from BUMDes,and 2) Describing the impact of digital marketing training from BUMDes Selo Angon Makmur in empowering people affected by the Covid 19 Pandemic in Tumpang Village, Talun Subdistrict, Blitar Regency. This method of devotion is PAR or Participatory Action Research. The subject of this service is bumdes selo angon makmur business partner community. The data collection techniques in this study use primary and secondary data. The data analysis techniques in this study use interactive analysis. The result of this service is in the form of training assistance from various parties to open marketing opportunities online market business withber forthe efforts of the village community and BUMDes. The impact of this training assistance results in advanced training to prepare various business development programs, one of which is preparing business training for the community such as; 1) Production Training and Business Feasibility. 2) Product Packaging Training. 3) Marketing training on business results and 4) financial management